Pengaruh Kinerja Lingkungan dan Struktur Kepemilikan terhadap Kinerja Keuangan dengan Pengungkapan Lingkungan sebagai Variabel Intervening - Vivian Angelina Soegiharto Wibowo; Teng Jesica Handoko (Universitas Widyatama, 2019)
Financial performance is the result of management's efforts in managing and carrying out operations using resources effectively in a given period. Financial performance is often used by stakeholders in making decisions, namely Return on Assets. In addition to financial performance, environmental performance is important for the company to preserve nature and prevent risks due to its operational activities. Implementation of good environmental performance requires substantial funds and funding that is often used, namely shares that create ownership structures. In return for investor funds, companies have an obligation to make disclosures, one of which is environmental disclosure. Environmental disclosure is expected to be able to show environmental performance and company ownership and this research environmental disclosure is used as an intervening variable.This study aims to obtain empirical evidence regarding the effect of environmental performance and ownership structure on financial performance with environmental disclosure as an intervening variable. The research population is all companies listed on the Indonesia Stock Exchange for the period 2015-2017 with purposive sampling, namely non-financial companies that obtain PROPER ratings and publish annual and financial reports on the IDX. This study uses SPSS 23 with secondary data and analyzed using regression analysis and path analysis.The results of his research are environmental performance has a positive effect on environmental disclosure and financial performance; institutional ownership has a negative effect on environmental disclosure and has no effect on financial performance; Managerial ownership has a negative effect on environmental disclosure, but has a positive effect on financial performance; foreign ownership has no effect on environmental disclosure and financial performance; environmental disclosure has no effect on financial performance; and environmental disclosure is not able to mediate environmental performance, institutional ownership, managerial ownership, foreign ownership of financial performance.